Archaeal overdominance close to life‐limiting conditions in geothermally influenced hypersaline lakes at the Danakil Depression, Ethiopia. (21st September 2021) - Belilla, Jodie; Iniesto, Miguel; Moreira, David; Benzerara, Karim; López‐García, José María; López‐Archilla, Ana I.; Reboul, Guillaume; Deschamps, Philippe; Gérard, Emmanuelle; López‐García, Purificación
Summary: The Dallol protovolcanic area on the Danakil Depression (Afar region, Ethiopia) exhibits unique hydrothermal manifestations in hypersaline context, yielding varied polyextreme physicochemical conditions. Previous studies identified a wide archaeal diversity in less extreme brines but failed to identify microorganisms thriving in either high‐chaotropicity, low‐water‐activity brines or hyperacidic‐hypersaline Na‐Fe‐rich brines. Recently, we accessed several small lakes under intense degassing activity adjacent to the Round Mountain, west to the Dallol dome [Western Canyon Lakes (WCL); WCL1‐5]. They exhibited intermediate parameter combinations (pH 5, 34%–41% (weight/volume) NaCl‐dominated salts with relatively high levels of chaotropic Mg‐Ca salts) that should allow to better constrain life limits. These lakes were overwhelmingly dominated by Archaea, encompassing up to 99% of prokaryotic 16S rRNA gene amplicon sequences in metabarcoding studies. The majority belonged to Halobacteriota and Nanohaloarchaeota, the latter representing up to half of prokaryotic sequences. Optical and epifluorescence microscopy showed active cells in natural samples and diverse morphotypes in enrichment cultures. Scanning electron microscopy coupled with energy‐dispersive X‐ray spectroscopy revealed tiny cells (200–300 nm diameter) epibiotically associated with somewhat larger cells (0.6–1 μm) but also the presence of silica‐dominated precipitates of similar size and shape, highlighting the difficulty of distinguishing microbes from mineral biomorphs in this kind of low‐biomass systems.